Penentuan Batas Minimum Circuit Breaker Di Sistem Kelistrikan Riau 150 KV - M. Ilham; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
On this paper, simulation of short circuit fault is performed on electrical power system of Riau. The simulation is performed by using power system analysis software DIgSILENT PowerFactory and use international standard IEC 60909 for short circuit calculation. The simulation is performed by giving three phase fault to 150 kV busses on electrical power system of Riau. The simulation results are three phase short-circuit current, it used to calculate the minimum capacity of circuit breaker and for the selection of circuit breaker. With the selection of circuit breaker according the standard, it can ensure that circuit breaker can work properly as function on break the short-circuit fault and the it’s not causing other damage on system. The final results showed that the minimum value circuit breaker capacity in riau electrical power systetem is variated base on the location of where the circuit breaker applied. The value of minimum circuit breaker on near generator is more greater than the far from generator. The highest value of safe or minimum circuit breaker capacity on Riau electrical system is 18.36 kA and the lowest is 2 kA. Keywords: short-circuit, minimum circuit breaker, DIgSILENT PowerFactory